2006
DOI: 10.1007/s00161-006-0035-4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic theory for smectic A liquid crystals

Abstract: A dynamic continuum theory is presented for smectic A liquid crystals in which the usual director n and unit layer normal a do not always necessarily coincide. Most previous dynamic continuum theories equate n with a; the theory developed in this article allows n and a to differ in non-equilibrium situations, work that has been motivated by the recent investigations by Auernhammer et al. (Rheol. Acta 39, 215-222, 2000; Phys. Rev. E 66, 061707, 2002) and Soddemann et al. (Eur. Phys. J. E 13, 141-151, 2004). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(83 citation statements)
references
References 35 publications
2
81
0
Order By: Relevance
“…The SmA dynamic theory of Stewart [33], which allows n and a to separate, will be summarized in section 2.1 before we go on to discuss, in section 2.2, the geometrical set-up and the particular model equations for a pressure-driven flow of SmA confined between two fixed parallel plates. It will be shown that there are three governing dynamic equations, given below by (2.29), (2.35), and (2.37), and it will be solutions to these equations that will be investigated subject to a symmetry requirement and suitable boundary conditions.…”
Section: Dynamic Theory and Description Of The Problemmentioning
confidence: 99%
“…The SmA dynamic theory of Stewart [33], which allows n and a to separate, will be summarized in section 2.1 before we go on to discuss, in section 2.2, the geometrical set-up and the particular model equations for a pressure-driven flow of SmA confined between two fixed parallel plates. It will be shown that there are three governing dynamic equations, given below by (2.29), (2.35), and (2.37), and it will be solutions to these equations that will be investigated subject to a symmetry requirement and suitable boundary conditions.…”
Section: Dynamic Theory and Description Of The Problemmentioning
confidence: 99%
“…These results track the subsequent response of the smectic to the refracted wave. Using the techniques of Landau and Lifshitz for sound in isotropic fluids [1], we extend the results for smectic C by Gill and Leslie [2] and perform the analogous calculations for a sample of smectic A using the dynamic theory of Stewart [3]. These calculations enable a comparison between the results for smectic A and an extension, by the present authors, to the known results for smectic C.…”
Section: Introductionmentioning
confidence: 69%
“…We now summarise the continuum theory in [3], in which n and a are allowed to separate, as considered by Ribotta and Durand [6]. The standard suffix notation for Cartesian vectors and tensors [7] is employed.…”
Section: Continuum Theory For Smectic a Liquid Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include certain alternate representations of Oseen-Frank in terms of dyadic tensors [2,10,21], generalizations of Oseen-Frank for nematics with nonuniform degree of orientational order [29,Chap. 6], several models of smectic liquid crystals (the second most common and important liquid crystal phase after the nematic) [27,28], and others. All of these models acquire an additional indefinite, saddle-point structure when they are coupled with an electric field, as discussed in the next section.…”
Section: Free Energy Modelsmentioning
confidence: 99%